Kandungan hara serta kemantapan agregat tanah akibat penambahan limbah pabrik kelapa sawit decanter solid pada Ultisol - Nuni Gofar; Diana Sinurat; Albertus Fajar Irawan (Fakultas Pertanian Universitas Yudharta Pasuruan, 2022)
Introduction: It is known that palm oil mills produce decanter solid as a byproduct in the form of organic solid waste. To test the opportunity to use decanter solid as a growing medium for oil palm seedlings, a study was conducted to evaluate, nutrient content, pH, and aggregate stability in media with different ratios of soil and decanter solid. Method: The design used in this study was a completely randomized design (CRD) consisting of 6 levels of treatment, namely A1 (1000 g soil + 0 g decanter solid), A2 (900 g soil + 100 g decanter solid), A3 (800 g soil + 200 g decanter solid), A4 (700 g soil + 300 g decanter solid), A5 (600 g soil + 400 g decanter solid), and A6 (500 g soil + 500 g decanter solid), and each the experimental unit was repeated 4 times. Result: The results showed that the addition of a decanter solid to Ultisol soil affected the pH value, macro and micro nutrient content and also improved soil aggregation. Conclusion: The best composition in increasing pH value, improving soil aggregation and increasing nutrient content is by mixing 40% decanter solid and 60% soil with an incubation time of 45 days.